THE RELATIONSHIP OF RHEUMATOID ARTHRITIS AND ANKYLOSING SPONDYLITIS WITH HEPATITIS B VIRUS - Saliha Karatay; Kadir Yıldırım; Meltem Alkan Melikoğlu; Kazım Şenel (Archives of Rheumatology, 2003)
Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are polyarthritic diseases which have multifactorial etiology. Also, it is reported that the hepatitis B virus (HBV) may be associated with polyarthritis. Therefore, 20 patients with RA, 26 patients with AS and 56 healthy controls were included in this study to investigate this relationship. Serological markers of HBV (Hbs Ag, Anti-Hbs, Anti-Hbc total, Anti- Hbc IgM, Hbe Ag and Anti-Hbe) were evaluated in all cases. No significant relation was found between these three groups for Hbs Ag and Anti-Hbs positivity (p> 0.05). The ratio of the coincide with HBV was increased in patients with RA when compared with healthy controls (45 % in the RA group, 21.4 % in the control group) (p< 0.05). As a result; it was concluded that the HBV may play a role in the etiology of RA.